2000
DOI: 10.1074/jbc.275.12.8416
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hepatic Very Low Density Lipoprotein Overproduction in Insulin Resistance

Abstract: A novel animal model of insulin resistance, the fructose-fed Syrian golden hamster, was employed to investigate the mechanisms mediating the overproduction of very low density lipoprotein (VLDL) in the insulin resistant state. Fructose feeding for a 2-week period induced significant hypertriglyceridemia and hyperinsulinemia, and the development of whole body insulin resistance was documented using the euglycemic-hyperinsulinemic clamp technique. In vivo Triton WR-1339 studies showed evidence of VLDL-apoB overp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(87 citation statements)
references
References 78 publications
(55 reference statements)
5
81
1
Order By: Relevance
“…The basis for accumulation of TG in the liver is complex and can include reduced assembly and secretion of VLDL because of defects in the synthesis of apoB (31) or in microsomal triglyceride transfer protein activity (32). However, VLDL assembly and secretion are typically increased above normal in animals (3,4,(33)(34)(35) and people (36 -39) with insulin resistance, diabetes mellitus, and hepatic steatosis, suggesting that other abnormalities are playing key roles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis for accumulation of TG in the liver is complex and can include reduced assembly and secretion of VLDL because of defects in the synthesis of apoB (31) or in microsomal triglyceride transfer protein activity (32). However, VLDL assembly and secretion are typically increased above normal in animals (3,4,(33)(34)(35) and people (36 -39) with insulin resistance, diabetes mellitus, and hepatic steatosis, suggesting that other abnormalities are playing key roles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, protein levels of FAS and SCD were increased in livers of apoB/BATless mice. Lipogenesis is a modest but significant source of TG for VLDL secretion in rodents (33,43) and in humans with obesity and insulin resistance (44,45). Studies from the laboratory of Goldstein and Brown have characterized in detail the role of the basic/ helix-loop-helix/leucine zipper transcription factor, SREBP1c, in the regulation of hepatic lipogenesis (8).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of expression of the Mtp gene in mice is associated with an absence of lipid droplets in the ER lumen (13) and defective secretion of apoB (13)(14). On the other hand, increases in MTP protein and activity are associated with increased assembly and secretion of apoB lipoproteins in mice (15) and hamsters (16). ApoB100 (4536 amino acids) is predicted to be comprised of an amino-terminal globular domain followed by three amphipathic ␣-helical domains alternating with two hydrophobic ␤ sheet domains (17).…”
Section: Microsomal Triglyceride Transfer Protein (Mtp)mentioning
confidence: 99%
“…Unlike livers from rat or mouse, the liver of the golden Syrian hamster secretes only apoB100-containing VLDL, and its lipoprotein metabolism more closely resembles that of humans (10). We have shown that insulin resistance in the fructose-fed golden Syrian hamster is associated with mild hypertriglyceridemia, VLDL-apoB oversecretion, increased intracellular apoB-containing lipoprotein particle stability, and increased expression of microsomal triglyceride transfer protein (MTP) (11). The present studies were conducted to explore the effect of improving insulin sensitivity in this insulin-resistant animal model by treatment with rosiglitazone, a peroxisome proliferator-activated receptor ␥ agonist and insulin sensitizer and to gain further insight into the molecular mechanisms of VLDL oversecretion in insulin resistant states.…”
mentioning
confidence: 99%